Pengelolaan Kelas dalam Pembelajaran Tematik Berbasis Google Classroom - Sumiati Pulungan (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This study aims to identify how the implementation of classroom management in thematic learning on the basis of google classroom. This study used a descriptive qualitative approach with a online method. This research was conducted in odd semester of fifth grade students at Al-Ulum Elementary School Medan. Sources of data in this study were teachers, thematic learning materials and lesson plans. Data collection techniques were by using observation, documentation and interviews. While the results of this study was thematic learning using the use of the google classroom application has proven to be very effective for teachers and students of fifth grade elementary school in a virtual system. Thematic learning by using the google classroom application was don by dividing into subjects.